Using legal tools in achieving social justice and peace: a look at the experience of Malaysia - Shuaib, Farid Sufian (2018)
Social justice is distribution of society’s advantages and disadvantages. It is the sharing of burdens and opportunities of members in a community. It requires consideration of resource equity, fairness and eradication of social oppression. The government may adopt social, political and legal initiatives in achieving social justice. Before and after the independence, Malaya was faced with guerrilla war fought against, among others, the Malayan Communist Party. There were also tensions between the difference races – particularly between the indigenous Malay and the then immigrant community of Chinese and Indian - caused primarily by the divide and rule policy of the colonial British. Faced with these challenges, the constitution for the newly independent Malaya have incorporated several provisions to ensure peaceful co-existence of the various races and followed by enactment of several laws. The creation of larger federation with the inclusion of Sabah, Sarawak and Singapore brought its own challenges to peace and resource sharing and thus requires further refinement of legislative instruments. Recently, with the conclusion of the 14th general election in Malaysia, a new coalition of political parties took power, which is the first time since the independence. The new coalition, Pakatan Harapan, departed from the traditional racial power sharing formula adopted by Barisan Nasional. Some of the policies of the new government with regard to social justice are different from the old government. This paper seeks to look at the legal instruments used to achieve peace, public order and social justice by the old and the new. Others probably could consider some of the experiences of Malaysia in working towards social justice and peace in the regional and global contexts.